2015
DOI: 10.2217/nnm.15.64
|View full text |Cite
|
Sign up to set email alerts
|

The Dartmouth Center for Cancer Nanotechnology Excellence: Magnetic Hyperthermia

Abstract: The Dartmouth Center for Cancer Nanotechnology Excellence – one of nine funded by the National Cancer Institute as part of the Alliance for Nanotechnology in Cancer – focuses on the use of magnetic nanoparticles for cancer diagnostics and hyperthermia therapy. It brings together a diverse team of engineers and biomedical researchers with expertise in nanomaterials, molecular targeting, advanced biomedical imaging and translational in vivo studies. The goal of successfully treating cancer is being approached by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Moreover, the overheating of cells can stimulate the anti-cancer immune response. Baker et al showed an increased response involving T lymphocytes in murine melanoma tissue following hyperthermia treatment [79]. In our studies, a substantial increase in temperature was observed for the composite sphere sample under the influence of an alternating magnetic field.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, the overheating of cells can stimulate the anti-cancer immune response. Baker et al showed an increased response involving T lymphocytes in murine melanoma tissue following hyperthermia treatment [79]. In our studies, a substantial increase in temperature was observed for the composite sphere sample under the influence of an alternating magnetic field.…”
Section: Discussionsupporting
confidence: 62%
“…Magnetic iron oxide nanoparticles (MNPs) have demonstrated utility in biomedical diagnosis and therapy because they display generally favorable biocompatibility and varied responsiveness to magnetic fields 1 10 . The search for nanoparticle constructs that preferentially accumulate in cancer tumors or cancer cells, after systemic delivery, remains an area of active research 11 15 . A successful strategy to develop selective targeting however requires knowledge of the relationship between nanoparticle structure and the resulting biologic activity between the physicochemical properties of nanoparticles and their impact on biological processes that affect the nanoparticle distribution throughout tissues and organs 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the studies that investigated a mouse model of melanoma, raising the temperature of tissue significantly improved the immune response with the participation of T lymphocytes. This therapy was applied before surgical resection and was directed at protecting against recurrences of tumors after removal and at helping to eliminate metastases [ 74 ].…”
Section: Summary Of Clinical Applications Of Spionsmentioning
confidence: 99%